Otorhinolaryngologic Evaluation of Patients with Obstructive Sleep Apnea Syndrome in Tertiary Hospital of Nepal - Shrestha, Inku; Dhakal, Subodh; Acharya, Sudeep; Bista, Meera (Journal of Karnali Academy of Health Sciences, 2021)
Background: Obstructive sleep apnea is a global health problem characterized by repeated partial or complete obstruction of the upper airways during sleep accompanied by nocturnal hypoxemia, interruptions during sleep and sleepiness during daytime. It is commonly associated with road traffic accidents, diabetes mellitus and cardiovascular disease. The study was aimed to measure the different otorhinolaryngologic parameters of patients with obstructive sleep apnea and to compare these findings with different classes of polysomnography. Methods: A hospital based cross-sectional study was carried out among patient coming to department of Otorhinolaryngology of Kathmandu Medical College and Teaching Hospital. In total, 74 patients with obstructive sleep apnea participated in this study. Sociodemographic details, co-morbid illness and anthropometric measurements were recorded. Data was presented in the form of mean, standard deviation and percentage. Chi-square, student’s t-test were done using Statistical Package for the Social Sciences version 21. A p-value of <0.05 was considered statistically significant. Results: The mean age of the patient was 47.43±11.30 years. Majority of the patients were male. Out of 74 patients, 24 (32.4%) patients were obese, 22 (29.7%) were overweight. The PSG showed 49 (66.2%) participants had severe obstructive sleep apnea. According to Modified Mallampati score, 28 (37.8%) of patients belonged to Class 3, 20 (27%) belonged to Class 2. There was no significant association observed between the studied variables and polysomnographic results. Conclusion: Male and old age were the predominant factor in obstructive sleep apnea patients. In patients with snoring, the Otorhinolaryngologist should rely on thorough medical history, anatomic examination of head and neck and polysomnography reports.